Is the world flat? Or do countries still matter? - Alberto Chong; Mark Gradstein (Inter-American Development Bank, Research Department, 2006)
This paper revisits the effects of a country's institutional framework on individual firms' behavior, in particular focusing on their propensity to comply with legal rules. The theoretical model presented here suggests that these effects may be of paramount significance-contrary to the recently popularized paradigm arguing that differences across countries have ceased to matter much. This paper's empirical strategy consists of explaining the variation in measures of noncompliance with legal rules and employs a rich dataset based on thousands of firms from dozens of countries. We find that most of the variation emanates from country-wide differences in institutional quality, although some firm characteristics play a role as well. Our conclusion is that countries still matter in providing institutional infrastructure, which determines to a large extent the context within which firms operate.
Keywords: D21; K42; O17; O57; 330; Firms; Institutions; Law compliance; Country differences; Globalization